Model-based assessment of nitritation using formic acid as a selective inhibitor. (10th December 2020) - Wang, Jipeng; Liu, Yongdi; Li, Wei
Abstract: Formic acid has been demonstrated to aid the rapid start-up and stable maintenance of nitritation (from ammonia to nitrite) in our previous work. In this work, a mathematical model integrated the decay and recovery of nitrifiers (including ammonia oxidizing bacteria (AOB) and nitrite oxidizing bacteria (NOB)) during and withdrawing formic acid treatment was established. The decay of nitrifiers was induced by the mixed inhibition (i.e. coexistence of competitive and non-competitive inhibition) of growth and the inactivation of substrate oxidation activity. Recovery of nitrifiers resulted from the relief and restoration of growth inhibition and substrate oxidation activity. The model was successfully evaluated by using data from independent batch experiments with different formic acid concentrations as well as from long-term bioreactor operation. The final model satisfactorily described the nitrogen conversion at the decay, recovery and stability stages. Modeling results showed formic acid had adverse effects on both activity and abundance of nitrifiers, while the rapid start-up of nitritation and rebound of ammonia oxidation performance were mainly attributed to the significant difference between AOB and NOB in the inactivation and recovery rate, respectively. Furthermore, the model suggested that shortened both the sludge retention time (<10 d) and hydraulic retention time (<7 h) were necessary to maintain the long-term stability of nitritation using formic acid. These results indicate the model built in this study will be a useful tool that allows for robust regulation of nitritation using formic acid. Highlights: Formic acid aided nitritation process was modeled. Mixed inhibition of formic acid on nitrifiers was revealed. Faster recovery of AOB than NOB favored the rapid achieving nitritation. SRT and HRT were crucial parameters for achieving the robust nitritation.